Analisis Implementasi Sistem Keuangan Desa (SISKEUDES) dalam Meningkatkan Akuntabilitas di Nagari Guguak Sarai - Arrum Komala Sari; Muhammad Wafiq; Dwila Maresti (Journal Of Business, Finance, and Economics (JBFE), 2025)
This study aims to analyze in depth the implementation of the Village Financial System (SISKEUDES) in an effort to improve financial management accountability in Guguak Sarai Village, Solok Regency. The research focuses on understanding the implementation process, the challenges faced, and the impacts on village governance. Using qualitative descriptive methods, data were collected through interviews with village officials, direct observation of financial management activities, and review of related documentation. The results indicate that the implementation of SISKEUDES can increase administrative efficiency, strengthen transparency, and improve the quality of the preparation and presentation of village financial reports. This system is considered to help make the recording, planning, and reporting processes more structured and easier to trace. However, its implementation still faces several obstacles, such as limited human resource competency, minimal training or outreach activities, and inadequate technological infrastructure. Overall, the use of SISKEUDES makes a significant contribution to improving the accountability of village financial management and supports the realization of good governance principles at the local level.